Analisis Korelasi antar Organ Tanaman Jambu Madu Deli Hijau - Nasihin, Muhammad; Fitri, M. Zaedan (Program Studi Agroteknologi, 2022)
Water guava is one type of fruit plant that contains quite a lot of nutrients, so it is very liked by most people. Deli honey water guava is one of the superior cultivars which is an introduced variety from Taiwan under the name Jade Rose Aple. This water guava has long been growing in North Sumatra for ± 10 years. The leaves on the water guava plant are included in the type of single leaf which are located scattered on the branches and twigs of the tree, the basic shape of the leaves is oval with a flat leaf edge. The tip of the leaf is blunt and the base is rounded which has a length of about 13-20 cm and a width of 5-7 cm. Water guava flowers are compound flowers, they are shaped like coral, located in the armpits of the leaves and the flower petals are funnel-shaped. Yellowish green flower color, stamens measuring 3.5 cm, white and there are more than 20 stamens. This research was conducted in Pancakarya Village, Ajung District, Jember Regency which was carried out on 26 September 2020 to 25 November 2020. The purpose of measuring the correlation between plant organs and plant productivity, the method used was correlation regression. Very low correlation occurs between branch length and diameter of the base, middle and tip as well as correlation between unit fruit weight and fruit diameter and fruit length.length). Keywords: Correlation, fruit, leaves, stems